SUKA ANGKA: GAME PEMBELAJARAN BERBASIS ANDROID GUNA MENINGKATKAN NUMERASI SISWA DI SEKOLAH DASAR - Hendri Irawan; Tutik Wijayanti; Andika Putra Pututama (STKIP Persada Khatulistiwa Sintang, 2022)
This study aims to develop an Android-based mathematics learning application for students of SD Negeri 02 Perjaya which is realized through valid, practical, and effective development. The discussion in this research is focused on the validity and practicality of using the application. The research model used is development research by following the development model according to Sugiyono (2011:408) with the following steps: (1) potential and problems, (2) data collection, (3) product design, (4) design validation, (5 ) product design revisions, (6) product trials. While the data analysis technique used is descriptive qualitative data analysis. The results of the study show (1) that a valid mathematical literacy structured learning application has been developed for elementary school students. Validity is compiled based on expert validation which states that the application developed can be applied and is in accordance with reality, namely meeting the valid criteria of content, construct, and language; and received good support and response by students.